Pengaruh Audit Tenure, Ukuran KAP, Spesialisasi Auditor, dan Auditor Switching Terhadap Kualitas Audit : (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Harry Budiantoro; Amanda Serena; Hestin Agus Tantriningsih (Journal of Research in Business, Economics, and Education, 2021)
This study aims to examine the influence of Audit Tenure, KAP Size, Auditor Specialization and Auditor Switching To Audit Quality This study uses a sample of manufacturing company listed on the Indonesia Stock Exchange (IDX) during the period 2017-2019. This type of research is a quantitative research. This study uses secondary data from the financial statement were obtained from the website Indonesian Stock Exchange (IDX). The analysis method of this research used was logistic regression with the SPSS Ver.25.0 application. The number of service companies in the manufacturing company which were used as samples of this study were 127 companies with 3-year observations. Based on the purposive sampling method, the total research sample is 381 financial statements. This study shows that Audit Tenure And Size KAP did not affect audit quality while auditor specialization had a positive effect on audit quality and auditor switching had a negative effect on audit quality.